Effects of Monobutyl and Di(n-butyl) Phthalate in Vitro on Steroidogenesis and Leydig Cell Aggregation in Fetal Testis Explants from the Rat: Comparison with Effects in Vivo in the Fetal Rat and Neonatal Marmoset and in Vitro in the Human - Hallmark, Nina (National Institute of Environmental Health Sciences, 2007)
BACKGROUND: Certain phthalates can impair Leydig cell distribution and steroidogenesis in the fetal rat in utero, but it is unknown whether similar effects might occur in the human. OBJECTIVES: Our aim in this study was to investigate the effects of di(n-butyl) phthalate (DBP), or its metabolite monobutyl phthalate (MBP), on testosterone production and Leydig cell aggregation (LCA) in fetal testis explants from the rat and human, and to compare the results with in vivo findings for DBP-exposed rats. We also wanted to determine if DBP/MBP affects testosterone production in vivo in the neonatal male marmoset. METHODS: Fetal testis explants obtained from the rat [gestation day (GD)19.5] and from the human (15–19 weeks of gestation) were cultured for 24–48 hr with or without human chorionic gonadotropin (hCG) or 22R-hydroxycholesterol (22R-OH), and with or without DBP/MBP. Pregnant rats and neonatal male marmosets were dosed with 500 mg/kg/day DBP or MBP. RESULTS: Exposure of rats in utero to DBP (500 mg/kg/day) for 48 hr before GD21.5 induced major suppression of intratesticular testosterone levels and cytochrome P450 side chain cleavage enzyme (P450scc) expression; this short-term treatment induced LCA, but was less marked than longer term (GD13.5–20.5) DBP treatment. In vitro, MBP (10(−3) M) did not affect basal or 22R-OH-stimulated testosterone production by fetal rat testis explants but slightly attenuated hCG-stimulated steroidogenesis; MBP induced minor LCA in vitro. None of these parameters were affected in human fetal testis explants cultured with 10(−3) M MBP for up to 48 hr. Because the in vivo effects of DBP/MBP were not reproduced in vitro in the rat, the absence of MBP effects in vitro on fetal human testes is inconclusive. In newborn (Day 2–7) marmosets, administration of a single dose of 500 mg/kg MBP significantly (p = 0.019) suppressed blood testosterone levels 5 hr later. Similar treatment of newborn co-twin male marmosets for 14 days resulted in increased Leydig cell volume per testis (p = 0.011), compared with co-twin controls; this is consistent with MBP-induced inhibition of steroidogenesis followed by compensatory Leydig cell hyperplasia/hypertrophy. CONCLUSIONS: These findings suggest that MBP/DBP suppresses steroidogenesis by fetal-type Leydig cells in primates as in rodents, but this cannot be studied in vitro.